Postmenopausal overactive bladder - Tomaszewski, Jacek (Menopause Review/Przegląd Menopauzalny, 2014)
Bladder storage symptoms have a severe impact on many areas as regards the quality of life including health-related, social, psychological and working functions. Pharmacotherapy of lower urinary tract stores (LUTS) has been developed to optimize neural control of the lower urinary tract in pathologic states. The bladder can be overactive or underactive. Overactive bladder (OAB) is highly prevalent and is associated with considerable morbidity, especially in aging population. Therefore, an effective treatment of OAB must result in a meaningful reduction in urinary symptoms. Pharmacotherapy for the OAB must be individualized based on the degree of bother, medication side-effect profile, concomitant comorbidities and current medication regimen. Antimuscarinic agents will continue to represent the current gold standard for the first-line pharmacological management of OAB. Alternatively to antimuscarinic therapy, 3-adrenergic receptor agonists, due to their efficacy and favorable adverse event profile, are a novel and attractive option of pharmacological treatment of overactive bladder symptoms. A combination of selective antimuscarinic and 3-adrenergic receptor agonists, agents with the different mechanism of action, gives a new treatment option for the patient with OAB according to its harms profile. A number of putative novel therapeutic agents is under clinical evaluations that may ultimately provide alternative or combination treatment options for OAB in the nearest future.